BUSINESS LEADERSHIP OF IT COMPANIES: IMPACT ON EMPLOYMENT AND SOCIO-ECONOMIC DEVELOPMENT OF THE COUNTRY - Poroshyn, Dmytro; Koy, Ayben; Khan, Bhola; Pakhnenko, Olena; Chvankin, Roman (Socio-economic relations in the digital society, 2024)
The relevance of the study is due to the influence of IT companies on the socio-economic development of the country. In the era of dynamic development of information and computer technologies, transnational corporations in the IT business are rapidly scaling up. Creating additional value in the industry due to the high level of education of certified, highly qualified specialists affects the positive economic growth of the country, where the share of IT companies is high. The article reflects the position of the largest corporations in the world, which take first place in terms of brand capitalization and market capitalization. Analysis of corporate income showed a close correlation with the number of the largest personnel. A study of corporations by field of activity showed the greatest specialization of companies in the development of computer programs. The analysis of the EU market reflected a close correlation between the dynamic development of the IT business over the past 10 years and especially in 2020 during the pandemic, but the negative trends of 2014 and 2022 also affected the indicators of IT companies, which after reducing staff in 2022-2023 received negative growth rates. Correlation-regression analysis of the impact of exports of IT products on services, the largest number of personnel reflected a direct correlation with the GDP of the EU country.Purpose and objectives of the study. The research method in the article is to determine the main trends in the global IT business and identify factors influencing the country's GDP. To identify the goal, the article conducted an analysis of IT by field of activity, geographical segments, an analysis of micro- and macroeconomic indicators of the industry, and the impact of the IT industry on the economic growth of the EU market using the method of correlation-regression analysis.The scientific novelty of the research results is brought to the identification of a correlation-regression relationship between the export of IT services and products, the main weight of the largest personnel in the industry and their impact on the GDP of the EU country.The practical significance of the research results lies in the study of the income of IT companies and the patterns of hiring ICT specialists.The results obtained in the article are formed on the basis of global databases TradeMap, Eurostat, Statista, Macrotrends, and analytical research by KPMG, which allowed us to reveal the goal and obtain an adequate economic and mathematical model.
Keywords: information and computer technologies; economic growth; market capitalization; ICT specialist